Meat yield and chemical composition of freshwater crab (Potamon persicum Pretzmann, 1962) - Karakaya, Suleyman; Karatepe, Pinar; Yalcin, Halil; Arslan, Ali (Ankara Univ, 2023)
In this study, morphometric measurement, meat yield, moisture, pH, protein, fat, fatty acids and ash content were determined in a total of 102 (15 female and 87 male) freshwater crab (Potamon persicum Pretzmann,1962) caught from Asagi and Yukari cay of Pertek, Tunceli. Meat yield in male and in female crabs were found to be as 12.75 +/- 0.38% and 10.93 +/- 0.32%, respectively. It has been observed that moisture and protein amounts were higher in female crabs than in male crabs. The amounts of fat were 0.96 +/- 0.31% in male crabs and 0.97 +/- 0.35% in female crabs. The amount of ash was 2.68 +/- 0.04% in male crabs and 2.66 +/- 0.03% in female crabs. It was determined that the content of monounsaturated fatty acids (female:male 33.56%:37.44%) in female and male crabs were higher than polyunsaturated (female:male 24.19%:21.62%) and saturated fatty acid (female:male 28.11%:32.85%) content. The highest fatty acid was found to be as omega-9, in terms of omega-3 (male crabs 8.54%, female crabs 14.85%), omega-6 (male crabs 10.04%, female crabs 5.46%) and omega-9 fatty acids (male crabs 23.65%, female crabs 19.14%) in freshwater crab (Potamon persicum Pretzmann, 1962) meat.
Potamon persicum Pretzmann,1962’nin et verimi ve kimyasal bileşimi
Keywords: Crab; Fatty acids; Meat yield; Omega-9; Protein